Monosubstituted ferrocene liquid crystals containing click triazole with a wide nematic phase temperature range. Issue 9 (15th July 2017) - Cheng, Haomin; Ma, Chao; Chen, Yao; Ni, Hai-liang; Feng, Chun; Wang, Bi-qin; Zhao, Ke-qing; Yu, Wen-hao; Hu, Ping
ABSTRACT: New monosubstituted ferrocenomesogens of the 1, 4-substituted-1, 2, 3-triazole series3a-3d and the 5-halogen-1, 4-substituted-1, 2, 3-triazole series4a-4d were successfully synthesised through a facile and versatile synthetic route using click reactions with moderate yields, in different atmospheres, and catalysed by different amounts of CuX (X = Br, I). Two series of compounds exhibited a typical nematic liquid crystal texture, and the 5-halogen-1, 4-substituted-1, 2, 3-triazole series4 had a wider mesomorphic temperature range than the corresponding series3 due to the effect of the halogen atom substituent on the triazole. These compounds showed similar absorption spectra, but the fluorescence emission spectra of4 were obviously redshift relative to3 . Cyclic voltammetry investigations revealed that the redox-active ferrocenyl groups of3 and4 follow one-electron transfer processes. GRAPHICAL ABSTRACT: